2020
DOI: 10.3390/ijms21155324
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Glioblastoma Multiforme—Exploration of Mitotic Catastrophe as a Potential Treatment Modality

Abstract: Glioblastoma multiforme (GBM) represents approximately 60% of all brain tumors in adults. This malignancy shows a high biological and genetic heterogeneity associated with exceptional aggressiveness, leading to a poor survival of patients. This review provides a summary of the basic biology of GBM cells with emphasis on cell cycle and cytoskeletal apparatus of these cells, in particular microtubules. Their involvement in the important oncosuppressive process called mitotic catastrophe will next be discussed al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 108 publications
(128 reference statements)
0
18
0
1
Order By: Relevance
“…In 2012, mitotic catastrophe was defined by the International Nomenclature Committee on Cell Death as an oncosuppressive mechanism that prevents the genomic instability of cells through the induction of mitosis-related cell death or permanent cell cycle arrest [ 23 ]. At least three mechanisms of mitotic catastrophe have been described: (I) Activation of the death machinery while the cell is still in mitosis; (II) “mitotic checkpoint adaptation,” i.e., arrested cells enter the interphase without chromosome segregation, and cell death is triggered at the following interphase; (III) development of the senescent phenotype after aberrant mitosis [ 24 , 25 ]. Depending on the status of cell cycle checkpoints, several cytotoxic agents could induce aberrant mitosis/mitotic catastrophe, activating different pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, mitotic catastrophe was defined by the International Nomenclature Committee on Cell Death as an oncosuppressive mechanism that prevents the genomic instability of cells through the induction of mitosis-related cell death or permanent cell cycle arrest [ 23 ]. At least three mechanisms of mitotic catastrophe have been described: (I) Activation of the death machinery while the cell is still in mitosis; (II) “mitotic checkpoint adaptation,” i.e., arrested cells enter the interphase without chromosome segregation, and cell death is triggered at the following interphase; (III) development of the senescent phenotype after aberrant mitosis [ 24 , 25 ]. Depending on the status of cell cycle checkpoints, several cytotoxic agents could induce aberrant mitosis/mitotic catastrophe, activating different pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of many microtubule inhibitors involves inhibition of the G2/M phase (Castro-Gamero et al, 2018). These drugs may be synergistic with the current standard of GBM therapy (temozolomide or radiotherapy) either by facilitating DNA damage or sensitizing malignant cells to standard therapy (Vitovcova et al, 2020). In future studies, we plan to explore the effect of the combination treatment of TBZ, TMZ and radiotherapy on GBM.…”
Section: Discussionmentioning
confidence: 99%
“…MC is a form of programmed cell death caused by the deregulation of mitotic process as an intrinsic onco-suppressive mechanism 2 , 3 . Studies have identified that DNA lesions, mitotic defects, failure of cytokinesis could cause MC, and even tumor cells are more susceptible to this mitotic abnormality than normal cells 4 , 5 . At present, in addition to photo and proton radiotherapy, there are a variety of chemotherapeutic drugs that could exert anti-tumor effects by inducing MC, covering microtubule regulators, CHK1 inhibitors, PARPs inhibitors, WEE1 inhibitors, PLKs inhibitors, and so on 6 , 7 , 8 , 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, in addition to photo and proton radiotherapy, there are a variety of chemotherapeutic drugs that could exert anti-tumor effects by inducing MC, covering microtubule regulators, CHK1 inhibitors, PARPs inhibitors, WEE1 inhibitors, PLKs inhibitors, and so on 6 , 7 , 8 , 9 , 10 . Currently, with the in-depth exploration of relevant studies on MC, the significance of MC in tumor prevention, treatment, drug resistance and radiosensitivity gradually developed 11 , 12 , 13 , 14 , which has attracted widespread attention from chemists to biologists in the fields of medicinal chemistry, molecular biology, and bioinformatics 5 , 15 , 16 , 17 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%